Microclimate Modification through Water Misting Increase Natural Enemy Insect Richness in a Cocoa Agroecosystem - Damayanti, Annisa; Windriyanti, Wiwin; Kusuma, Ramadhani Mahendra (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze the influence of abiotic factors on the diversity of natural enemies in cocoa fields. The study was conducted from January to March 2025. Various traps were used, including yellow traps, light traps, pitfall traps, and visual observations. Identification showed that cocoa fields with misting applications had a higher number of natural enemies (1,052 individuals) compared without misting fields (658 individuals). The application of misting resulted in higher diversity indices (H’), richness (R’), and dominance (C’), as well as lower evenness (E’) compared to untreated fields. These findings suggest that the misting system creates a more favorable microhabitat for natural enemy diversity, thus potentially strengthening the IPM approach in cocoa cultivation. Interestingly, the analysis showed that temperature had a significance value (sig) > 0.05, indicating that temperature did not show a significant correlation with the increase in the abundance of natural enemies, while humidity has a significance value (sig) < 0.05, which shows that humidity has a significant correlation, although statistically relatively small, with the increase in the abundance of natural enemies.